INFORMATION-ORIENTED AND KNOWLEDGE-ORIENTED SOCIETIES: THE CORRELATION OF NOTIONS - Онопрієнко, М. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The complicated disposition of such notions as “information-oriented society” and “knowledge-oriented society” arises from the differences between information and knowledge.